Essays on Development and Health Economics: Social Media and Education Policy - Jiang, Qin (online, 2021)
This dissertation consists of three essays on development economics and health economics. The first chapter examines the impact of social media usage on depressive symptoms in the United States. The use of social media can potentially decrease the level of depressive symptoms by providing support or increase the level of depressive symptoms by putting social pressure on users. This chapter leverages a fixed-effects model to estimate the effect of using social media platforms on depressive symptoms. I find that using Twitter decreases the level of depressive symptoms by 27%. This result explains why social media usage in the US has grown steadily even though most studies found that more usage correlated with higher levels of depressive symptoms. There is heterogeneity with respect to age, income, education, race, previous level of depressive symptoms, and region. The average labor market benefit that comes from this effect is equivalent to 0.1% GDP in the US.In the second chapter, I examine the performances of different bias correction methods, such as matching and weighting methods, on improving the representativeness of social media data. I find that matching and weighting methods can effectively improve the representativeness of social media users in most cases examined. Matching methods with smaller number of neighbors or smaller radius produce smaller biases. Improving the representativeness of Twitter users is easier than improving the representativeness of Facebook users.The third chapter is a collaboration with Yinan Liu, in which we study the impact of the primary school starting age policy in China on both short-run and long-run outcomes. We examine the household characteristics of the right age group, early group, and late group based on the compliance. Starting school late is negatively associated with cognitive skills, test scores, highest education achieved and income. We also explore the potential explanations why a large proportion of households send children to primary school before they reach the eligible age in China.
Keywords: Graue Literatur; Hochschulschrift; Aufsatzsammlung; Depressive symptoms; Matching; School starting age; Selection bias; Social media; Weighting